Existence of a Solution to an Infinite System of Weighted Atangana-Baleanu Fractional Integral Equations via Measure of Non-Compactness on a Tempered Sequence Space - Yeasmin, Fahmida Nishat; Ahmed, Tazuddin (Communications in Mathematics and Applications, 2025)
The goal of this study is to investigate the existence of a solution of an infinite system of weighted Atangana-Baleanu fractional integral equations via a newly constructed generalised form of the Darbo’s fixed-point theorem on a tempered sequence space. Furthermore, an example has been illustrated to demonstrate the effectiveness of the result obtained.
Keywords: Measure of Noncompactness (MNC); Fixed Point Theorems (FPT); Fractional Integral Equation (FIE)